Palaeoenvironment and organic matter of the Triassic Chang 9 lacustrine shales, Ordos Basin, China. (8th December 2019) - Xu, Zhengjian; Liu, Luofu; Jiang, Shu; Wang, Tieguan; Fang, Chao; Zhang, Zhihuan; Wu, Kangjun; Feng, Yanjun; Dou, Wenchao
Abstract : The Ordos Basin, a large mainly non‐marine basin, is an important petroliferous basin in northern China. The Triassic Chang 9 shales, including the delta plain shale (DPS), delta front shale (DFS), and deep lake shale (DLS), are proven to be the main source rocks in the lower Yanchang Formation (LYF). This study investigates the source rock potential, palaeoenvironment, and organic matter (OM) source. According to the OM thermal maturity, abundance, and type, the shales have excellent source rock potential. The DLS has the highest quality with average TOC of 7.08%, S1 + S2 of 14.41 mg HC/g rock, and Type II1 –II2 . According to correlations of Rb/Sr versus Sr/Cu, the shales were mainly deposited in arid conditions. Based on the major element (S), trace elements (V, Ni, Co, Cr, U, and Th), rare earth element (Ce) concentrations, and biomarkers (Pr, Ph, dibenzofuran, fluorene, and dibenzothiophene), redox conditions for the DPS, DFS, and DLS were oxidizing, sub‐oxidizing to sub‐reducing, and reducing, respectively. The palaeosalinity was fresh‐ to brackish‐water, ascertained by the trace elements (Sr and Ba) and biomarkers (gammacerane). The water stratification was controlled by the temperature changes and the palaeosalinity differences, and the maximum water depth was ~100 m during the Chang 9 deposition. Aquatic microorganisms (e.g., algae, bacteria, and phytoplankton) were the main organic matter sources for the shales, mixed together with terrigenous plants in DPS and DFS. The DLS has the most aquatic microorganisms and has the least higher plant fragments, supported by the higher TOC (up to 14%), lowest vitrinite contents (Avg. = 14.1%), and highest liptinite contents (Avg. = 59.5%). Laterally, the DPS, DFS, and DLS were distributed successively from the lake margin to the depocentre. Vertically, the DLS, DFS, and DPS were developed successively from the bottom lake to the upper lake. The DLS was mainly formed in an environment of high‐level sapropelinite and favourable preservation conditions, and the DPS was mainly formed in an environment of high‐level terrigenous inputs and poor preservation conditions, while the DFS was mainly formed in an environment of medium‐level of sapropelinite productivity and terrigenous inputs and fair preservation conditions. The DPS and DFS were formed during both the early stage (shallow lake) and the late stage (deep lake) of the Chang 9 deposition, while the DLS was only developed in the deep lake during the late Chang 9 deposition. The high‐level sapropelinite production and favourable preservation controlled the formation of the organic‐rich shales, especially for the organic‐rich DLS.